FENOMENA DAKWAH EKS-HTI PASCA DIBUBARKAN - Fitriyana, Siti Nur (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Walisongo Semarang, 2019)
This paper talking about phenomenon of ex-HTI as forbidden mass organization that is khilafah ideologically. Its existence in Indonesia is still developed through all media, print media and new media. Print media (bulletin) that shaded by ex-HTI is subscribed by the community. This is proven by the total production of print media (bulletin) to reach 10.000 eksemplar for distributed in Indonesia and then which is no less important is use of new media to show dakwah of ex-HTI related to khilafah still working massively. This could be proven by many posts on each social media account, that is to reach 849 posts. Both media discuss about the khilafah. The results of this research shows that all media shaded by ex-HTI changes the movement name become GP (Gerakan Pembebasan), BMI (Back To Muslim Identity), and Muslimah News Id. Technique data collection uses documentation and interview. This research concludes that dakwah activities of ex-HTI about khilafah are massive and structured. This is seen from social media account managed by ex-HTI that is Â still posting the content of khilafah which are expeted to be enforced.Â Â